Relationship between morphological traits and milk yield in Gir breed cows - Lagrotta, Marcos Rodrigues; Euclydes, Ricardo Frederico; Verneque, Rui da Silva; Júnior, Mário Luiz Santana; Pereira, Rodrigo Junqueira; Torres, Robledo de Almeida (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to determine genetic parameters related to morphological traits and their genetic correlation with milk yield of Gir breed cows. A total of 3,805 records from 2,142 cows was used. For morphological trait analysis, the used model included the herd fixed effects, classification year and season, lactation phase and animal age at evaluation, besides the classifier identification. For milk yield, the fixed herd effects, year and season of calving and cow age at calving were included in the model. The genetic parameters were estimated using the REMLF90 software. The heritability estimates varied from 0.09 to 0.54. The additive genetic variability of the majority of traits is sufficient to achieve significative annual genetic gain by selection practices. The genetic correlations among morphological traits varied from low to high and, between them and milk yield, from low to moderate. High genetic correlations among some morphological traits implies on the possibility of exclusion of some of them from the breeding program, for Gir breed in Brazil. The genetic correlations between milk yield and some morphological traits indicate that they may be used in the formation of selection indexes.